EVALUATION OF Pseudomonas aeruginosa ACTIVITIES OF MUNG BEAN (Vigna radiata) SEED EXTRACT - Usman, Aminu; Kutawa , Abdulaziz B.; Musa, Danladi D.; Danmallam, Faruq Ahmad (FUDMA JOURNAL OF SCIENCES, 2025)
This research focused on exploring of mung bean seed extracts and its potential as antibacterial agents. Mung bean (Vigna radiata) is a warm-season legume originally from the Indian subcontinent, where it was domesticated around 1500 BC. It is now cultivated widely across Asia, Africa, and the Americas due to its adaptability to diverse climates and soils. They are widely recognized for their high nutritional value and medicinal properties. The study was motivated by the increasing global concern over antimicrobial resistance and the need for natural alternatives to synthetic antibacterial agents. The research began with the collection of mung bean seeds from northern Nigeria, followed by their extraction using polar (ethanol) solvent. The extraction process aimed to evaluate the antibacterial efficacy of the mung bean extracts, antibacterial assays was conducted using the agar-well diffusion method against Pseudomonas aeruginosa. The results showed that the mung bean extracts exhibited significant inhibitory effects on the bacterial pathogens, with the largest zones of inhibition observed at higher extract concentrations. The study further analyzed the statistical significance of these results using an ANOVA, which confirmed that the antibacterial activity was consistent across different concentrations, although the differences between the concentrations were not statistically significant. The study also highlighted the potential of mung beans in food preservation, given their consistent antibacterial activity across different concentrations.